(untitled) (Docentes 2.0 Journal, 2024)
Mindfulness, derived from Buddhist Vipassana meditation, involves paying conscious, non-judgmental attention to the present moment, promoting full awareness. The objective of the study was to examine the impact of Mindfulness-Based Cognitive Therapy on anxiety associated with the consumption of psychoactive substances. The research was based on the pragmatic paradigm, with a mixed research approach, contemplating a method based on a case study and a pre-experimental design. The selected patient met the criteria established for the investigation. Mindfulness-Based Cognitive Therapy techniques were applied along with Beck’s Substance Use Therapy, complemented with descriptive schemes that included a functional diagnosis, modeling scheme, self-concept, and attributional scheme to improve the understanding of the case and carry out the appropriate intervention. for the patient. At the beginning, a battery of tests was administered to evaluate the patient’s anxiety levels, repeating them at the end to verify the reduction of these levels, which revealed a significant decrease in discomfort. The results indicated a positive impact of the Mindfulness-based program on the patient’s anxiety management. This conclusion suggests the effectiveness of Mindfulness-Based Cognitive Therapy as an intervention to address anxiety related to the use of psychoactive substances.